2016
DOI: 10.1155/2016/7950781
|View full text |Cite
|
Sign up to set email alerts
|

Shuyu Capsules Relieve Premenstrual Syndrome Depression by Reducing5-HT3ARand5-HT3B

Abstract: The effects of the Shuyu capsule on 5-HT3AR and 5-HT3BR expression in a rat model of premenstrual syndrome (PMS) depression and on 5-HT3AR and 5-HT3BR expression and hippocampal neuron 5-HT3 channel current were investigated, to elucidate its mechanism of action against PMS depression. PMS depression model rats were divided into depression and Shuyu- and fluoxetine-treated groups, which were compared to control rats for frontal lobe and hippocampal 5-HT3AR and 5-HT3BR expression and behavior. The depressed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Though our behavioral experiments revealed that fluoxetine and BXD had a similar effect on the PMDD model, some studies have shown different effects. Some studies have shown that the active compounds in BXD could ease most of symptoms of PMDD ( Lee et al, 2008 ; Nizamutdinova et al, 2008 ; Peng et al, 2010 ; Zhou et al, 2011 ; Xie et al, 2015 ), while other studies showed that fluoxetine was mainly to treat PMDD depression ( Francois et al, 2003 ; Sarkisova and Folomkina, 2010 ; Li et al, 2016 ), which is only one subtype of PMDD; these results suggest that BXD could be active on multiple targets. Through analysis of the 6 signal regulatory pathways influenced by BXD capsules, we found that BXD can alter PMDD irritability by influencing various intercellular and intracellular signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though our behavioral experiments revealed that fluoxetine and BXD had a similar effect on the PMDD model, some studies have shown different effects. Some studies have shown that the active compounds in BXD could ease most of symptoms of PMDD ( Lee et al, 2008 ; Nizamutdinova et al, 2008 ; Peng et al, 2010 ; Zhou et al, 2011 ; Xie et al, 2015 ), while other studies showed that fluoxetine was mainly to treat PMDD depression ( Francois et al, 2003 ; Sarkisova and Folomkina, 2010 ; Li et al, 2016 ), which is only one subtype of PMDD; these results suggest that BXD could be active on multiple targets. Through analysis of the 6 signal regulatory pathways influenced by BXD capsules, we found that BXD can alter PMDD irritability by influencing various intercellular and intracellular signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the chip results, demonstrating the reality and reliability of the chip results as well. Besides, another traditional Chinese medicine, Shuyu capsule, which was found to reduce 5-HT 3A R and 5-HT 3B R expression ( Li et al, 2016 ) and has some of the same herbal ingredients as BXD, was seen to effectively treat PMDD depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, exclusion of females could be a significant point against this study’s clinical relevance because depression and anxiety are more prevalent in women than in men. Actually, we noticed that some subtypes of depression or anxiety were related to fluctuating hormones [ 92 , 93 ]. Evaluating only male offspring could focus more on the “passing on” behavioural deficits caused by maternal chronic SDS.…”
Section: Discussionmentioning
confidence: 99%
“…Shuyu capsule is a kind of Chinese medicine developed by our research group, mainly containing active principle from Radix Bupleuri, rhizoma cyperi, Radix Paeoniae Alba and liquorice. It has been studied in a rat model of premenstrual syndrome depression that Shuyu capsules rectified abnormal 5-HT 3 AR and 5-HT 3 BR expression and 5-HT 3 channel current changes in a rat model ( 14 ). But no pathway alterations was revealed related to depression.…”
Section: Introductionmentioning
confidence: 99%